Prolong Omeprazole Therapy Impacts on Biochemical Parameters in Peptic Ulcer Disease Patients (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Prolonged use of proton pump inhibitors (PPIs) is associated with a range of potential adverse effects. Omeprazole, one of the most widely prescribed PPIs globally, is commonly used in clinical practice.Objective: To assess the impact of prolonged omeprazole use on specific biochemical markers in individuals receiving treatment for a year or more.Methods: This case-control study was conducted in the Department of Physiology of Armed Forces Medical College, Dhaka Cantonment using data obtained from at the Department of Medicine (Gastroenterology), Kurmitola General Hospital, Dhaka from October 2023 to March 2024, enrolling 122 participants; 62 patients diagnosed with uncomplicated peptic ulcer disease (PUD) (32 females, 30 males) and 60 age- matched healthy controls (30 females, 30 males)-selected from individuals aged 30 to 65 years presenting with epigastric symptoms and confirmed as diagnosed case of PUD through upper gastrointestinal endoscopy.Results: While high-density lipoprotein levels were unaffected (p>0.05), prolonged use of omeprazole was related to significant increases in triglycerides, cholesterol and low-density lipoprotein levels (p0.05), however there were elevated levels of alkaline phosphatase (p=0.001) and aspartate aminotransferase (p=0.001). Further, the group treated with omeprazole had significantly higher creatinine levels (p=0.001). Serum ferritin and calcium levels were also significantly lower (p